Alva and Gunnar Myrdal in Sweden and America, 1898-1945 - Jackson, Walter A., author.
1 online resource.
Keywords: "Alva and Gunnar Myrdal are the only couple ever awarded Nobel prizes as individuals: Gunnar won the prize in Economics in 1974, and Alva won the Peace Prize in 1982. This dual biography examines their work as architects of the modern welfare state and probes the connections between the public and private dimensions of their lives. Drawing on their extensive personal correspondence and diaries between their electrifying first meeting in 1919 and their protracted marital crisis in the early 1940s, this book presents the psychologist and the economist as they sought to combine love and work in an equal partnership. Alva and Gunnar simultaneously experimented with a new kind of intimate relationship and designed the social supports necessary for women both to bear and raise children and to contribute their talents and energies to society. Like all genuine revolutionaries, they struggled to free themselves from the burdens of their upbringings; to evaluate their own actions with what they called "unsparing honesty," and to test their policy recommendations in practice, measuring everything against the values they shared"--